Caesarean section in four South East Asian countries: reasons for, rates, associated care practices and health outcomes - Henderson-Smart David J; Ewens Melissa R; Pattanittum Porjai; Laopaiboon Malinee; Festin Mario R; Crowther Caroline A (BMC, 2009)
Abstract Background Caesarean section is a commonly performed operation on women that is globally increasing in prevalence each year. There is a large variation in the rates of caesarean, both in high and low income countries, as well as between different institutions within these countries. This audit aimed to report rates and reasons for caesarean and associated clinical care practices amongst nine hospitals in the four South East Asian countries participating in the South East Asia-Optimising Reproductive and Child Health in Developing countries (SEA-ORCHID) project. Methods Data on caesarean rates, care practices and health outcomes were collected from the medical records of the 9550 women and their 9665 infants admitted to the nine participating hospitals across South East Asia between January and December 2005. Results Overall 27% of women had a caesarean section, with rates varying from 19% to 35% between countries and 12% to 39% between hospitals within countries. The most common indications for caesarean were previous caesarean (7.0%), cephalopelvic disproportion (6.3%), malpresentation (4.7%) and fetal distress (3.3%). Neonatal resuscitation rates ranged from 7% to 60% between countries. Prophylactic antibiotics were almost universally given but variations in timing occurred between countries and between hospitals within countries. Conclusion Rates and reasons for caesarean section and associated clinical care practices and health outcomes varied widely between the four South East Asian countries.